ANALYSIS OF ELEMENTARY SCHOOL STUDENTS' PROBLEM-SOLVING ABILITIES IN SOLVING STORY PROBLEMS ON SOLID GEOMETRY BASED ON GENDER - Farada, Nadifa; Habibie, Zulqoidi R. Habibie; wati, Mega (Prima: Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the problem-solving abilities of elementary school students in solving story problems related to spatial geometry, as viewed from gender differences. The approach used is descriptive qualitative, with 128 students from several elementary schools in Muara Bungo City who have studied spatial geometry as the research subjects. The research instrument consists of an essay test designed based on four problem-solving ability indicators, namely: (1) understanding the problem, (2) developing a solution plan, (3) solving the problem according to the plan, and (4) reviewing the results obtained. Data were collected through tests, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing stages. The research results showed differences in strategies and achievements between male and female students on each indicator. Female students excelled in the indicators of understanding the problem and reviewing the results of their work, with characteristics of high accuracy and consistency in verifying answers. Conversely, male students were more prominent in the indicators of developing a solution plan and solving problems according to the plan, tending to choose quick and practical strategies. These differences reflect the influence of psychological characteristics and thinking styles specific to each gender. These findings are expected to serve as a reference for teachers in designing mathematics learning strategies that accommodate the strengths of both genders so that all students can optimize their problem-solving abilities.